BLACK AMERICAN LIFE REFLECTED IN LANGSTON HUGHES' POEMS: A SOCIOLOGICAL APPROACH - WIDIASTUTI , AFISTA (2007)
The major problem of this study is to reveal how does black American life in existence of inequality and slavery reflected in Langston Hughes' poems on sociological approach. The objectives of the study are to analyze the poems based on its structural elements and to analyze the poems based on sociological approach. The writer conducts the researcher by using a qualitative method. It means a library research, while data source is the literary, the data are divided into two categories, primary and secondary data. The primary data is the text of Langston Hughes' poems entitled LET AMERICA BE AMERICA AGAIN, WILL V-DAY BE ME DAY TOO?, FREEDOM PLOW, FREEDOM TRAIN and DEMOCRACY taken from selected poems of Langston Hughes. The secondary data sources are other source such as essay, comments, historical information, biography of internet and other relevant information. The data collection is literary research. The technique of the data analysis is descriptive. The outcome of the study shows: firstly, there is a close relationship between a work of literature and sociological phenomena. Secondly, in these poems, Langston Hughes wants to say that social relation between the white and the black in America society.